Literature Analysis of Traditional Chinese Medicine Syndrome of Helicobacter Pylori-related Gastropathy - Tan, Ying Xze (2015)
Background of Research: HP are the most common bacterial infection that usually treated by using antibiotics. Recent years, researchers have been reporting that for being ineffective and causing side effects due to the resistance of antibiotics. Literature Reviews: HP has various clinical manifestations, and its aetiology and pathogenesis are complex. However, the relationship between TCM syndrome type and HP still lacks systemize analysation. Objectives: To make preliminary conclusion through literature analysis on the classification of TCM syndrome of HP related Gastropathy. Research Methodology: Through Chinese journal full-text database (CNKI) to retrieve TCM Syndrome of HP related gastropathy in the modern medical journal, forming database of TCM syndrome on HP associated gastropathy, conducting descriptive statistical analysis on distribution of commonly seen TCM syndrome of HP related gastritis. Results: HP TCM Syndrome mainly divided to Damp-Heat Obstruction on Middle Burner Syndrome 27.74%, Liver Depression Qi Stagnation Syndrome 18.71%, Weakness of Spleen and Stomach Syndrome 17.69%, Middle Burner Weakening with Qi Stagnation Syndrome 8.19%, Liver Depression with Stomach Heat Syndrome 7.84%, Stomach Yin Deficiency Syndrome 6.02%, Spleen Deficiency with Stomach Heat Syndrome 3.83%, Stomach Collateral Blood Stagnation Syndrome 3.72%, Spleen Deficiency Dampness Accumulation Syndrome 2.76%, Stomach Heat Accumulation Syndrome 2.65%, Cold and Heat Complication Syndrome 0.85%, Phlegm and Heat Intermingled Syndrome 0.59%, Food Stagnation at Stomach and Intestine Syndrome 0.53%, Spleen Deficiency Damp-Heat Syndrome 0.26%, cold Pathogen attack Stomach Syndrome 0.11%, Qi and Yin Deficiency Syndrome 0.06%. Conclusion: HP infection belongs to the category of “pathogenic Qi” in TCM, can be ascribed to “Damp-Heat” pathogen that is the six evils of the TCM. Hp related gastropathy is characterized by “asthenia in origin but sthenia at superficial”, sthenia for the internal accumulation of dampness and heat pathogen, liver depression and qi stagnation, stomach heat accumulation and blood stasis stagnates at stomach collaterals, while asthenic for weak spleen and stomach and Yin Blood asthenia.